Tourists’ perception of Gaborone as a tourist destination - Kemang, Kamogelo Olga; Sechele-Mosimanegape, Phetogo; Mkwizu, Kezia Herman (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2023)
Destinations all over the world have been affected by the COVID-19 pandemic and Gaborone as a tourist destination faces challenges of branding and marketing strategies. The main aim of this paper is to explore tourists’ perception of Gaborone as a tourist destination from the tourists’ point of view. Specifically, this paper has two specific objectives which are to explore the perceptions of tourists on the brand image of Gaborone city as a tourist destination, and to explore the perception of tourists on the brand identity of Gaborone city as a tourist destination. The study location is Gaborone city in Botswana. A total of 50 tourists as a sample size. The methodology used was quantitative. The usable questionnaire for analysis were 35 and subjected to descriptive analysis. The findings have shown that there were different perceptions by tourists regarding the image and identity of Gaborone city as a tourist destination. Most of the international tourists (over 50%) agreed that brand image included aspects such as unique climate, safety and security while brand identity revealed that the slogan “Diamond City of the World” was attractive and also, services offered at different sites are of high quality. Hence, this study’s outcome is helpful to business communities, destination planners and Destination Marketing Organizations (DMOs) to consider brand image and identity as marketing strategy tools to attract visitors.